Single-nucleotide polymorphism rs1058205 of KLK3 is associated with the risk of prostate cancer: A case–control study of Han Chinese men in Northeast China - Chen, Chen; Xin, Zhongqiu (Medicine (Baltimore), 2017)
Prostate cancer (PCa) is a serious public health concern for men worldwide. However, the risk factors for PCa remain largely unclear. Aim of this study was to investigate statistical associations between the risk of prostate cancer and the rs1058205 single-nucleotide polymorphism (SNP) of the KLK3 gene, which encodes the prostate specific antigen (PSA), in a case-control study of Han Chinese men in Northeast China. Using a high-resolution melting curve genotyping method, we determined the genotype and allele distributions of rs1058205 in 2 groups of Han Chinese men, consisting of 268 PCa patients and 298 healthy control subjects. Logistic regression was used to evaluate associations between rs1058205 genotypes and the risk of PCa. Tumor staging and Gleason score were included in a stratified analysis of PCa risk. The frequency of the TC genotype of rs1058205 in the PCa group was significantly lower than that in the control group (P = 0.049). The serum PSA level in participants with the TC genotype was significantly lower than that of the TT and CC genotypes in both the PCa and control groups (P < 0.010 for both). The TT genotype was associated with PCa, both with and without adjustment for age (P < 0.010 and P = 0.047, respectively). The TT genotype was also associated with the moderate- and high-risk PCa categories (P = 0.007 and 0.027, respectively). The TT genotype may represent a useful biomarker for identifying high risk of PCa and as a postoperative prognosticator in Chinese PCa patients.